Remaking the news essays on the future of journalism scholarship in the digital age - Boczkowski, Pablo J.; Anderson, C. W. (Christopher William) 1977- (Cambridge, Massachusetts The MIT Press, 2017)
The use of digital technology has transformed the way news is produced, distributed, and received. Just as media organizations and journalists have realized that technology is a central and indispensable part of their enterprise, scholars of journalism have shifted their focus to the role of technology. Leading scholars chart the future of studies on technology and journalism in the digital age. These ongoing changes in journalism invite scholars to rethink how they approach this dynamic field of inquiry. The contributors consider theoretical and methodological issues; concepts from the social science canon that can help make sense of journalism; the occupational culture and practice of journalism; and major gaps in current scholarship on the news: analyses of inequality, history, and failure.--Editor's summary
Includes bibliographical references and index.
Keywords: Journalism -- Technological innovations; Electronic newspapers -- Technological innovations